Investigation of trap levels in HgCdTe IR detectors through low frequency noise spectroscopy. (26th January 2016) - Ciura, L; Kolek, A; Kębłowski, A; Stanaszek, D; Piotrowski, A; Gawron, W; Piotrowski, J
Abstract: Low frequency noise spectroscopy is a valuable tool for studying narrow gap semiconductor materials and devices. In the paper, the method of traps investigation with low frequency noise spectroscopy was presented, together with quantitative analysis of the results obtained for high-operating-temperature, fast response, Hg1− x Cd x Te mid-wavelength infrared detectors. The hole trap levels in these devices are Cd-content independent and take the value E T ≅ 140 meV or E T ≅ 40 meV. The level at E T ≅ 140 meV was found for almost all tested detectors. The level around E T = 40 meV was found in two samples. Apart from the hole traps, three electron traps were also found. Their energy levels follow the trend lines E T = 0.35 E g ( x ) and E T = 0.75 E g ( x ). All trap energies are consistent with the results reported in the literature for Hg1− x Cd x Te devices.